Experimental investigation of partially premixed combustion in a DISI natural gas engine: Performance, Combustion behaviour, and Crevice hydrocarbons - Jeffrey C. Galbraith; James S. Wallace (Energy Conversion and Management: X)
The use of partially premixed combustion (PPC) can overcome current limitations of natural gas (NG) fuelled engines. Experimental results are presented for NG PPC in a spark ignited single cylinder research engine. Injection timing of directly injected NG was varied from the beginning of the compression stroke to just before top dead centre (BTDC). Decreasing time available for mixing before ignition resulted in increasingly stratified mixtures as injection approached TDC. The study’s goals were: To explore the stable operating range for a flat plane NG injector and for a cone pattern injector with a 100 degree included angle, to demonstrate the impact of injection timing on piston top land crevice emissions for the two injector nozzles through analysis of cycle-by-cycle exhaust port hydrocarbon (HC) measurements, and to highlight the effect of NG injection timing on fuel supply pressure requirements. Injected fuel residence time between the end of injection and ignition had a critical influence on combustion behaviour for both nozzles. The cone nozzle confined fuel to the piston bowl at earlier injection timings, reducing crevice penetration and expanding the feasible operating range. Optimal operation was achieved with the cone nozzle at 33–34 crank angle degrees (CAD) residence time, corresponding to 66 and 73 CAD BTDC injection timings for 34 and 69 kPa gauge intake pressures respectively. At the optimal operating point, indicated mean effective pressure (IMEP) increased 21.0 and 39.5% and HC from crevice outgassing decreased by 76.4 and 60.9% for the two intake pressures respectively relative to premixed operation.